2014
DOI: 10.1002/hrm.21611
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a Means of Reducing Perceptions of Work‐Family Conflict: A Test of the Roles of Self‐Efficacy and Psychological Strain

Abstract: Prior research suggests that exercise has positive benefits for individuals and the organizations they work for. Using the literature related to social cognitive theory and exercise, the present study hypothesizes and tests the effects of exercise on two directions of work‐family conflict: work interference with family (WIF) and family interference with work (FIW). Using a sample of 476 working adults, we found that exercise was both positively related to self‐efficacy for managing work‐family conflict and neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 102 publications
(155 reference statements)
1
14
1
1
Order By: Relevance
“…Instead, people who live a more harmonic life and who are more psychologically available to invest in multiple roles can develop an outward focus that makes them more inclined to engage fully in life and appreciate what work and nonwork (family, sport, or community) roles can offer. This is likely to engender positive energy as the outward focus may counteracts the selffocused attention that is responsible for low energy (Clayton, Thomas, Singh, & Winkel, 2014;Rothbard, 2001). Thus, Hypothesis 4: Psychological availability will mediate the relationships between WLB and employees' positive energy.…”
Section: Wlb Psychological Availability and Positive Energymentioning
confidence: 85%
“…Instead, people who live a more harmonic life and who are more psychologically available to invest in multiple roles can develop an outward focus that makes them more inclined to engage fully in life and appreciate what work and nonwork (family, sport, or community) roles can offer. This is likely to engender positive energy as the outward focus may counteracts the selffocused attention that is responsible for low energy (Clayton, Thomas, Singh, & Winkel, 2014;Rothbard, 2001). Thus, Hypothesis 4: Psychological availability will mediate the relationships between WLB and employees' positive energy.…”
Section: Wlb Psychological Availability and Positive Energymentioning
confidence: 85%
“…Problems of time conflict can be addressed with programs that increase workplace flexibility of time or space (e.g., schedule control [Schieman & Young, 2010]) or provision of resources that can add support to family life (e.g., convenience of child care [Payne, Cook, & Diaz, 2012]). Problems of strain can be addressed, obviously, by reducing the root causes of strain, but also with stress-reduction techniques such as exercise (Clayton, Thomas, Singh, & Winkel, 2015), child caregiver attentiveness (Payne et al, 2012), and social support from the employer (Kelly et al, 2014). Behavior-based conflict, though, requires the development of skills that work well in the given environment as well as the ability to recognize which skills are appropriate in varied circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…As alluded to earlier, a number of studies examining the relation between WFC and physical activity have concluded that individuals experiencing WFC exercise less (Allen & Armstrong, ; Caudroit, Boiché, Stephan, Le Scanff, & Trouilloud, ; Roos, Sarlio‐Lähteenkorva, Lallukka, & Lahelma, ). One possible explanation for these findings is that individuals who already experience difficulty fulfilling their work and family responsibilities do not feel that exercise is a worthwhile use of free time, and instead, believe free time is better spent getting ahead on work and family tasks (Caudroit et al, ; Clayton, Thomas, Singh, & Winkel, ). Alternatively, these findings could be attributable to WLC draining employees’ resources.…”
Section: Health Behaviorsmentioning
confidence: 99%
“…Ironically, research suggests that moderate levels of physical activity throughout the day could actually strengthen individuals’ beliefs in their ability to handle WFC (Clayton et al, ). In fact, such activity has been found to ameliorate some of the negative effects WFC has on overall health (Clayton et al, ; Lee et al, ; Singh, Suar, & Leiter, ), thereby allowing individuals to continue meeting their work and family obligations. Researchers attribute this result to physical activity acting as a recovery mechanism that restores mental and physical resources, making individuals more productive and efficient (Lee et al, ).…”
Section: Health Behaviorsmentioning
confidence: 99%